Modern methods of repairing architectural monuments in Uzbekistan - Islamov Feruz Xashimovich (Zien Journals, 2022)
This article discusses modern methods of repairing architectural buildings in Uzbekistan
Keywords: Historical monument, cities, object, architecture, architectural style